Infrastructure development as a catalyst for sustainable economic growth in OIC countries - Amiliana, Vina; Suliswanto, Muhammad Sri Wahyudi (Jurnal Ekonomi & Studi Pembangunan, 2025)
Infrastructure development plays an important role in promoting sustainable economic growth, especially in member countries of the Organization of Islamic Cooperation (OIC). The purpose of this study is to understand how different types of infrastructure, such as digital, physical and non-physical infrastructure, investment, investment and human development index (HDI) impact sustainable economic growth. This study uses data from 52 OIC member countries over the period 2022-2023. To analyse the data, a statistical method called Estimated Generalized Least Squares (EGLS) is used, which is specifically designed to overcome differences in conditions between countries in the data. This method helps to obtain more accurate results despite the imbalance or variation of data between countries. The results of this study show that non-physical infrastructure and HDI have a positive and significant influence on sustainable economic growth. Non-physical infrastructure, such as institutions and basic services can help strengthen the economic system. HDI also plays an important role in improving the quality of human resources. Meanwhile, physical infrastructure, digital infrastructure and investment have not shown a significant direct effect. Therefore, it is recommended that the governments of OIC countries focus on strengthening institutions and improving diverse human qualities to support inclusive and sustainable economic growth.